2018
DOI: 10.1002/kin.21191
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical investigation of the reaction of RO2 radicals with OH radicals: Dependence of the HO2 yield on the size of the alkyl group

Abstract: The HO2 yield in the reaction of peroxy radicals with OH radicals has been determined experimentally at 50 Torr helium by measuring simultaneously OH and HO2 concentration time profiles, following the photolysis of XeF2 in the presence of different hydrocarbons and O2. The following yields have been obtained: ϕ CH 3O2 = (0.90 ± 0.1), ϕC2H5O2 = (0.75 ± 0.15), ϕC3H7O2 = (0.41 ± 0.08), and ϕC4H9O2 = (0.15 ± 0.03). The clear decrease in HO2 yield with increasing size of the alkyl moiety can be explained by an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 46 publications
7
60
0
Order By: Relevance
“…An upper limit of 5% for the yield of Criegee radicals was also determined by Assaf et al (2017), in agreement with the theoretical expectation that it should be negligible (Müller et al, 2016). A yield of 0.9±0.1 for the methoxy + HO 2 channel was determined experimentally at low pressure (50 Torr) (Assaf et al, 2018), in good agreement with the best theoretical Torr). Those results imply however a methanol yield much lower than the value (0.23) used in our global model to reconcile its predictions with atmospheric methanol observations at remote locations (Müller et al, 2016).…”
Section: Ch 3 O 2 + Ohsupporting
confidence: 85%
See 2 more Smart Citations
“…An upper limit of 5% for the yield of Criegee radicals was also determined by Assaf et al (2017), in agreement with the theoretical expectation that it should be negligible (Müller et al, 2016). A yield of 0.9±0.1 for the methoxy + HO 2 channel was determined experimentally at low pressure (50 Torr) (Assaf et al, 2018), in good agreement with the best theoretical Torr). Those results imply however a methanol yield much lower than the value (0.23) used in our global model to reconcile its predictions with atmospheric methanol observations at remote locations (Müller et al, 2016).…”
Section: Ch 3 O 2 + Ohsupporting
confidence: 85%
“…Those results imply however a methanol yield much lower than the value (0.23) used in our global model to reconcile its predictions with atmospheric methanol observations at remote locations (Müller et al, 2016). Note that at low pressure (as used in the experiments by Assaf et al (2017) and Assaf et al (2018)), stabilisation of the trioxide is negligible, given the quadratic dependence of the stabilisation fraction (f stab ) on atmospheric pressure (Müller et al, 2016),…”
Section: Ch 3 O 2 + Ohmentioning
confidence: 55%
See 1 more Smart Citation
“…In OH-initiated VOC oxidation, RO 2 is primarily produced via VOC + OH → R (+H 2 O) followed by R + O 2 → RO 2 , where R is hydrocarbyl or oxygenated hydrocarbyl radical. Since the second step is extremely fast in air (Atkinson and Arey, 2003), the first step controls the RO 2 production rate, which depends on OH concentration and OHR ext due to VOCs (OHR VOC ; see Appendix B for details). OHR VOC also includes the contribution from oxidation intermediates of primary VOCs (e.g., methyl vinyl ketone and pinonic acid).…”
Section: Ro 2 Production and Loss Pathwaysmentioning
confidence: 99%
“…Praske et al (2018) measured RO 2 isomerization rate constants at 296 and 318 K and observed an increase in the rate constants by a factor of ∼ 5 on average. A 15 K temperature increase in OFRs would lead to RO 2 isomerization being accelerated by a factor of ∼ 3, while other major gas-phase radical reactions have weak or no temperature dependence (e.g., ∼ 7 %, ∼ 5 %, ∼ 6 % and ∼ 19 % slowdowns for isoprene+OH, toluene + OH, typical RO 2 + NO and RO 2 +HO 2 , respectively; Atkinson and Arey, 2003;Ziemann and Atkinson, 2012). As a consequence, the relative importance of RO 2 isomerization in RO 2 fate in OFRs can be elevated and closer to atmospheric values (Fig.…”
Section: Guidelines For Ofr Operationmentioning
confidence: 99%